Investigation into the effect of process parameters on microstructural and physical properties of 316L stainless steel parts by selective laser melting - Steve Brown (The International Journal of Advanced Manufacturing Technology, 2015)
Additive manufacturing by selective laser melting (SLM) was used to investigate the effect of laser energy density on 316L stainless steel properties. Point distance and exposure time were varied and their impact on porosity, surface finish, microstructure, density and hardness, was evaluated. The surface roughness was primarily affected by point distance with increased point distance resulting in increased surface roughness, R a, from 10 to 16 μm. Material hardness reached a maximum of 225 HV at 125 J/mm3 and was related to the material porosity; with increased porosity leading to decreased material hardness. Different types of particle coalescence leading to convex surface features were observed (sometimes referred to as balling); from small ball features at low laser energy density to a mixture of both small and large ball features at high laser energy density. Laser energy density was shown to affect total porosity. The minimum amount of porosity, 0.38 %, was observed at an energy density of 104.52 J/mm3.